2018
DOI: 10.1016/j.chom.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and Temporal Changes in the Gut Microbiome of Pediatric Ulcerative Colitis Patients Are Linked to Disease Course

Abstract: Summary Evaluating progression risk and determining optimal therapy for ulcerative colitis (UC) is challenging as many patients exhibit incomplete responses to treatment. As part of the PROTECT (Predicting Response to Standardized Colitis Therapy) Study, we evaluated the role of the gut microbiome in disease course for 405 pediatric, new-onset, treatment-naive UC patients. Patients were monitored for one year upon treatment initiation, and microbial taxonomic composition was analyzed from fecal samples and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
194
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(218 citation statements)
references
References 52 publications
21
194
0
3
Order By: Relevance
“…Crucially, intestinal inflammation is correlated with elevated or “pathological” cell shedding, which is also correlated with altered microbiota profiles 13-15 . Previous studies have indicated that antibiotic usage, and antibiotic‐induced microbiota perturbations, particularly in infancy, are linked to increased risk of developing inflammatory disorders in later life 16 . More recently, research, including our own, has shown important links between members of the intestinal microbiota and the cell shedding response in vivo, demonstrating that early life members of the gut microbial community (ie, Bifidobacterium ) can drive protection against pathological cell shedding in adult mice 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…Crucially, intestinal inflammation is correlated with elevated or “pathological” cell shedding, which is also correlated with altered microbiota profiles 13-15 . Previous studies have indicated that antibiotic usage, and antibiotic‐induced microbiota perturbations, particularly in infancy, are linked to increased risk of developing inflammatory disorders in later life 16 . More recently, research, including our own, has shown important links between members of the intestinal microbiota and the cell shedding response in vivo, demonstrating that early life members of the gut microbial community (ie, Bifidobacterium ) can drive protection against pathological cell shedding in adult mice 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…Crucially, intestinal inflammation is correlated with elevated or 'pathological' cell shedding, which is also correlated with altered microbiota profiles [12][13][14]. Previous studies have indicated that antibiotic usage, and antibiotic-induced microbiota perturbations, particularly in infancy, are linked to increased risk of developing inflammatory disorders in later life [15]. More recently, research, including our own, has shown important links between members of the intestinal microbiota and the cell shedding response in vivo, demonstrating that early life members of the gut microbial community (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…30 Widespread changes in the gut microbiota, including lower diversity and decreased abundance of putatively beneficial bacteria, such as Lachnospiraceae, have been demonstrated in both UC and CDI. 31, 32 Lachnospiraceae is a primary producer of butyrate, which is known to inhibit C. difficile in vitro 33 and enhances intestinal epithelial barrier function. 34 Furthermore, both C. difficile and Lachnospiraceae are taxonomically classified within the Clostridiales order.…”
Section: Discussionmentioning
confidence: 99%